2019
DOI: 10.1016/j.isci.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Regulation of HuR by Translation Repression and Protein Degradation Determines Pulsatile Expression of p53 Under DNA Damage

Abstract: Summary Expression of tumor suppressor p53 is regulated at multiple levels, disruption of which often leads to cancer. We have adopted an approach combining computational systems modeling with experimental validation to elucidate the translation regulatory network that controls p53 expression post DNA damage. The RNA-binding protein HuR activates p53 mRNA translation in response to UVC-induced DNA damage in breast carcinoma cells. p53 and HuR levels show pulsatile change post UV irradiation. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 52 publications
0
46
0
2
Order By: Relevance
“…It is curious that HO2 protein degradation levels plateau at around 50%, a phenomenon that is not unique to HO2 (25,26). We propose that, since HO2 possesses critical cytoprotective functions, an unknown factor(s) is induced to protect it from further degradation when a threshold low cellular concentration is reached.…”
Section: Resultsmentioning
confidence: 97%
“…It is curious that HO2 protein degradation levels plateau at around 50%, a phenomenon that is not unique to HO2 (25,26). We propose that, since HO2 possesses critical cytoprotective functions, an unknown factor(s) is induced to protect it from further degradation when a threshold low cellular concentration is reached.…”
Section: Resultsmentioning
confidence: 97%
“…As TRIM21 has been shown to interact with HuR and mediates ubiquitination-dependent proteasomal degradation of HuR under genotoxic stress 26 , we sought to understand in more detail the cellular function of TRIM21 in the context of DNA damage. We found that TRIM21 knockdown abrogates the decrease of HuR post 4 h of UV exposure (Fig.…”
Section: Trim21 Reverses the Decrease In Cell Proliferation And Colonmentioning
confidence: 99%
“…TRIM21 also promotes the proliferation of osteosarcoma cells and its expression enhances the tolerance of osteosarcoma cells to various stresses 25 . It also affects the expression and stability of p53 in different cancers [26][27][28] . Recently, TRIM21 has been shown to cause the temporally-regulated degradation of the RNA-binding protein HuR in response to UVC irradiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of Hur and Trim21 (Guha et al, 2019) were used as used as positive controls and 249 secondary antibodies against ATP7B (anti-rabbit) and VPS35 (anti-goat) were used as negative 250 controls. We observed positive interaction between ATP7B and VPS35 that is evident by 251 formation of red intracellular puncta on sites if the two proteins juxtapose at a distance less than 252 <40nm ( Fig 7F).…”
mentioning
confidence: 99%